The Wolverine Project: Evaluating Cumulative Effects Within the Land of Ktunaxa Using the One Heart Method - Nikki Heim; Ryan MacDonald; Christopher Horsethief; Chad Luke; Michael Proctor; Marlene Machmer; Vi Birdstone; Ray Warden; Curtis Wullum; Rachel Plewes; Matthew Chernos; Matt Carlson (Environmental Management, 2025)

Quota use in mixed‐stock fisheries - William A. Karp; Michael C. Melnychuk; Robyn E. Forrest; Lorne Richard Little; Kristin McQuaw; Chad Demarest; Ray Hilborn; Nicole Baker; Brian Mose; Bruce Turris; Ernesto Penas Lado (Fish and Fisheries, 2024)
Although most fisheries assessment and management focuses on the status of individual stocks, and regulations are commonly established as single‐species total allowable catch limits (TACs), much of the catch from global fisheries comes from mixed‐stock fisheries where species cannot be harvested separately. We show that in some fisheries where TAC and catch of demersal fish stocks are tracked, the average fraction of TAC harvested ranges from 21% to 68% overall and is declining. This is, in part, related to efforts to protect all species from overfishing, leading to ‘choke species’, which limit fishing pressure on other target species. While some choke species arise from a mix of low and high‐productivity species, others result from allocation processes, which can be aggravated by shifting distributions due to climate change. Underutilization of TACs can also result from market limitations, low value of individual species, undercapacity or management measures. Proposed methods for increasing long‐term yield require species to be managed in stock groups, or allowing the abundance of some stocks to fall below target reference points. We suggest that the observed low and declining aggregate harvests are due, primarily, to the focus on single‐stock sustainability measures, rather than performance of the fisheries in relation to potential overall yield. While there is a growing consensus that single‐species management should be replaced by an ecosystem‐based approach, this will require clear legislative directives regarding management of the trade‐offs involved. Time series considered in this analysis do not extend beyond 2019.

Considerations for Soluble Protein Biomarker Blood Sample Matrix Selection - Joel A. Mathews; Yan G. Ni; Connie Wang; Jon E. Peterson; Chad Ray; Xuemei Zhao; Daoyu Duan; Sara Hamon; John Allinson; Martha Hokom; Greta Wegner (The AAPS Journal, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Workshop Report: Crystal City VI—Bioanalytical Method Validation for Biomarkers - Mark E. Arnold; Brian Booth; Lindsay King; Chad Ray (The AAPS Journal, 2016)

Feasibility of Singlet Analysis for Ligand Binding Assays: a Retrospective Examination of Data Generated Using the Gyrolab Platform - Tracey H. Clark; Phillip D. Yates; Allison Given Chunyk; Alison P. Joyce; Aidong Wu; Petar Pop-Damkov; Yiqun Zhang; Elizabeth A. Dreher; Laurie A. Tylaska; Jo-Ann A. Wentland; Kathleen B. Pelletier; Lindsay E. King; et al. (The AAPS Journal, 2016)

Ligand Binding Assays in the 21st Century Laboratory—A Call for Change - Chad A. Ray; Ago B. Ahene (The AAPS Journal, 2012)

Ligand Binding Assays in the 21st Century Laboratory: Platforms - Franklin P. Spriggs; Zhandong Don Zhong; Afshin Safavi; Darshana Jani; Narasaiah Dontha; Anita Kant; Jenny Ly; Lia Brilando; Karolina Österlund; Nathalie Rouleau; Saloumeh Kadkhodayan Fischer; Martin Boissonneault; et al. (The AAPS Journal, 2012)

Fit-for-Purpose Method Development and Validation for Successful Biomarker Measurement - Jean W. Lee; Viswanath Devanarayan; Yu Chen Barrett; Russell Weiner; John Allinson; Scott Fountain; Stephen Keller; Ira Weinryb; Marie Green; Larry Duan; James A. Rogers; Robert Millham; et al. (Pharmaceutical Research, 2006)